Implications for the Accession Countries of the Rejection of the EU Constitution - Georges de Menil (Romanian Journal of European Affairs, 2005)
The rejection of the EU Constitutional Treaty by the French and Dutch electorates has profound implications for the European Union, its existing members and its accession candidates. The two referenda indicate that public opinion in Western Europe is more wary of deeper European integration and more anxious about enlargement than had seemed the case in the euphoria of May, 2004. The leaders of the existing Union are, therefore, likely to proceed more cautiously on both fronts. In some cases, accession will be postponed, in many the doors to immigrant workers will be partially closed, in all, structural funds in support of accession risk being reduced.